God is not great : the case against religion - Hitchens, Christopher (London : Atlantic Books, 2007)
Talks about the role of religion in the world. This book states that religion is man made, a cause of dangerous sexual repression and a gross distortion of our origins in the cosmos. It marvels at the possibility of society without religion, arguing instead that the concept of an omniscient God has profoundly damaged humanity.
Includes bibliographical references and index.
Keywords: Religion; Religion and ethics; Religion and sociology